Cross-Talk Between Extracellular Matrix and Skeletal Muscle: Implications for Myopathies - Ahmad, Khurshid; Shaikh, Sibhghatulla; Ahmad, Syed Sayeed; Lee, Eun Ju; Choi, Inho (Frontiers in Pharmacology, 2020)
Skeletal muscle (SM) comprises around 40% of total body weight and is one of the most important plastic tissues in the human body, as it supports skeletal development, controls body temperature, and manages glucose levels. Extracellular matrix (ECM) maintains the integrity of SM, enables biochemical signaling, provides structural support, and plays a vital role during myogenesis. A number of human diseases are associated with dysfunctions of the ECM, and several ECM components are involved in disease pathologies that affect almost all organ systems. Thus, mutations in ECM genes that encode proteins and their transmembrane receptors can result in diverse SM diseases, a large proportion of which are types of fibrosis and muscular dystrophy. In this review, we present major ECM components of SMs related to muscle-associated diseases, and discuss two major ECM myopathies, namely, collagen myopathy and laminin myopathies, and their therapeutic managements. A comprehensive understanding of the mechanisms underlying these ECM-related myopathies would undoubtedly aid the discovery of novel treatments for these devastating diseases.